Information sur les marchés : Rétablir l'équilibre - Centre Technique de Coopération Agricole et Rurale (Technical Centre for Agricultural and Rural Cooperation, 2009)
Farmers can use market information to contact buyers and reduce the number of people involved in bringing their produce to consumers.